MiR‐204‐5p suppresses hepatocellular cancer proliferation by regulating homeoprotein SIX1 expression. Issue 2 (15th January 2018) - Chu, Yi; Jiang, Mingzuo; Du, Feng; Chen, Di; Ye, Tao; Xu, Bing; Li, Xiaowei; Wang, Weijie; Qiu, Zhaoyan; Liu, Haiming; Nie, Yongzhan; Liang, Jie; et al.
Abstract : Fewer than 30% of patients with hepatocellular carcinoma (HCC) are eligible to receive curative therapies, and so a better understanding of the molecular mechanisms of HCC is needed to identify potential therapeutic targets. The role of microRNA (miRNA) in modulating tumour progression has been demonstrated, and therapies targeting miRNA appear promising. miR‐204‐5p has been shown to function in numerous types of cancer, but its role in HCC remains unclear. In this study, we found that miR‐204‐5p expression was downregulated in cancerous HCC tissues compared to nontumour tissues. Kaplan–Meier survival curve analysis also showed that low expression of miR‐204‐5p predicted worse outcomes of HCC patients. In addition, miR‐204‐5p expression was significantly lower in HCC cell lines. The function of miR‐204‐5p was also assessed both in vitro and in vivo . We demonstrated that ectopic expression of miR‐204‐5p in HCC cell lines inhibited HCC cell proliferation and clonogenicity using CCK8, BrdU and colony‐forming assays, while the inhibition of miR‐204‐5p enhanced proliferation and clonogenicity. Further in vivo studies in mice further confirmed the proliferation capacity of miR‐204‐5p. We also identified sine oculis homeobox homologue 1 ( SIX1 ) as a direct target of miR‐204‐5p and showed that it was inversely correlated with miR‐204‐5p in both human and mouse HCC tissues. Transfection of miR‐204‐5p mimics in BEL‐7404 cells blocked the cell cycle by inhibiting the expression of cyclin‐D1 and cyclin‐A1, cell cycle‐related factors regulated by SIX1. More importantly, overexpression of the 3′UTR mutant SIX1 but not the wild‐type SIX1 abolished the suppressive effect of miR‐204‐5p, and downregulated SIX1 in BEL‐7402 cells that transfected with miR‐204 inhibitors could partly block the inhibitory effect of miR‐204‐5p on proliferation. Thus, we have demonstrated that miR‐204‐5p suppresses HCC proliferation by directly regulating SIX1 and its downstream factors. Abstract : More treatment options for hepatocellular carcinoma (HCC) are needed, and therapies targeting microRNA (miRNA) appear promising. In this study, we analysed the role of miR‐204‐5p in HCC. We demonstrated that miR‐204‐5p expression is downregulated in HCC. Functional and mechanistic studies showed that miR‐204‐5p suppressed HCC proliferation by directly regulating sine oculis homeobox homologue 1 (SIX1) and its downstream factors.